PEMBERDAYAAN UMKM UNTUK PENGEMBANGAN PRODUK OLAHAN LOKAL DI DESA AMBULU KECAMATAN SUMBERASIH - Rahmansyah, Ahmad Iskandar; Rahman Wiyono, Agung Abdul; Cahyono, Davit; Ridwan, Mohammad (Jurnal Pengabdian Masyarakat Sabangka, 2025)
Empowerment of Micro, Small, and Medium Enterprises (MSMEs) in Ambulu Village, Sumberasih Subdistrict, Probolinggo Regency, was conducted through direct assistance by the KKN 11 team from Universitas Panca Marga. This activity included the creation of visual promotional media such as banners, digitalization of business locations using Google Maps, and digital marketing training for MSME actors like tofu factories, laundry services, spice milling, and catering businesses. The results showed an increase in business visibility in the digital world, a rise in new customers, and growing motivation among MSME actors to manage their businesses independently. The main challenges identified were limited digital literacy and technological infrastructure, which require attention for program sustainability. This study provides an MSME empowerment model based on the integration of conventional promotional media and digitalization that can be replicated in other areas.